How to draw dinosaurs in simple steps - Palmer, Dandi (Tunbridge Wells Search, 2012)
The step-by-step way to learn how to draw a fantastic collection of dinosaurs
Drawing
1
Keywords: Dinosaurs in art; Drawing -- Technique